Evidence for the participation of beta1-adrenoceptors in isoprenaline-induced renin release from rat kidny slices in vitro. - Desaulles, E (1978)
1. The inhibitory effects were studied of 4 beta-adrenoceptor antagonists against renin release induced by isoprenaline (0.5 mumol/1) in rat kidney slices. Additionally the pA2 values of these 4 drugs were measured against isoprenaline in guinea-pig isolated atria and trachea (against beta1- and beta2-adrenoceptors respectively). 2 When employed at a concentration of 2 mumol/1 propranolol and atenolol significantly inhibited renin release (P less than 0.001 and P less than 0.01) whereas practolol and IPS 339 [t-butyl-amino-3 ol-2 propyl) oximino-9 fluorene] had little effect. 2 A positive correlation was shown between the degree of inhibition of renin release and the pA2 of the antagonists at the beta1-adrenoceptors. 4 When practolol and IPS 339 were used in equipotent molar concentrations to propranolol for the beta1-adrenoceptors they inhibited renin release. 5 The results suggest that the adrenoceptor involved in the renin release induced by isoprenaline in the rat kidney is of the beta1-type.